Pengaruh Electronic Word of Mouth dan Promosi Terhadap Proses Keputusan Pembelian Youtube Membership Kobolonimbus - Cahyani, Aprillia Regita; Muzayanah, Fety Nurlia (Jurnal Ilmiah Wahana Pendidikan, 2023)
"The Influence of Electronic Word of Mouth and Promotion on thePurchasing Decision Process of Kobolonimbus Youtube Membership".Under the guidance of Fety Nurlia Muzayanah SE., M.Sc. S1 ManagementProgram, Faculty of Economics, University of Singaperbangsa Karawang.This study aims to determine the partial and simultaneous significant effectof electronic word of mouth and promotion on the Purchase DecisionProcess of kobolonimbus membership youtube. The research is quantitativewith descriptive and verification analysis and uses non-probability samplingpurposive sampling techniques. The sample in this study were members ofthe Kobolonimbus Youtube Membership who were buying or had bought aKobolonimbus YouTube membership, totaling 384 respondents. the dataused is primary data resulting from distributing questionnaires which arethen processed using SPSS for windows 21. The data is processed using amultiple linear regression analysis model. Hypothesis testing was carried outusing the t test and f test. The results of this study show that electronic wordof mouth and promotion have a partial and simultaneou